Warriors [compact disc] - Miranda, Lin-Manuel, 1980- (Atlantic, 2024)
From Amazon.com: "Warriors, the new project from Lin-Manuel Miranda and Eisa Davis, is a concept album inspired by the 1979 Paramount Pictures cult film, "The Warriors," based on the Sol Yurick novel of the same name. Warriors is executive produced by Grammy Award winning rapper & New York City native Nas & produced by Grammy Award winning musician Mike Elizondo. Warriors is an immersive listening experience that follows a fictitious New York City gang from Coney Island to the Bronx and back when they are framed for the murder of a respected gang leader, Cyrus."